2013
DOI: 10.1016/j.matchemphys.2013.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of Co-doped titanate nanotubes and their optical sensitization with methylene blue

Abstract: Here we report on a novel chemical route to synthesize homogenous cobalt doped titanate nanotubes (CoTNT), using an amorphous Co-doped precursor. The influence of the synthesis temperature, autoclave dwell time and metal doping on the structural and microstructural as well as on the optical properties of the synthesized titanate nanotubes is studied and discussed. The optical band gaps of the CoTNT samples are red shifted in comparison with the values determined for the undoped samples, such red shifts bringin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…S1). 15 For the 5% cobalt modified samples, i.e. Co(5%)-TNT and TNT/Co(5%) samples, the presence of the Co in addition to Ti, O and Na elements was confirmed by EDS (not shown).…”
Section: Structural and Morphological Characterizationmentioning
confidence: 93%
See 3 more Smart Citations
“…S1). 15 For the 5% cobalt modified samples, i.e. Co(5%)-TNT and TNT/Co(5%) samples, the presence of the Co in addition to Ti, O and Na elements was confirmed by EDS (not shown).…”
Section: Structural and Morphological Characterizationmentioning
confidence: 93%
“…Among them, titanate nanotubes (TNT) are remarkable materials since they combine the conventional properties TiO 2 nanoparticles, with the properties of layered titanates, such as photocatalytic activity and ion-exchange ability. [12][13][14][15] Additionally they have an open mesoporous morphology with a higher specific surface area than TiO 2 , which is a very important parameter for surface-based applications such as photocatalysis. Despite their high charge recombination rate and wide bandgap (ca.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Santara et al investigate the high temperature ferromagnetism of Co.-doped TiO 2 nanoparticles, which prepared by using a ball milling method [35]. Ferriera et al reported the synthesis of Co.-doped titanate nanotubes synthesized by hydrothermal method and study its adsorption ability with methylene blue [36]. It was shown that Co.-doped titanate has higher dye sensitization as compared with undoped titanate.…”
Section: Introductionmentioning
confidence: 99%